Fatal intrusion : a novel [large type] - Deaver, Jeffery; Maldonado, Isabella, 1965- (Thorndike Press large print high octane., 2024)
Homeland Security agent Carmen Sanchez and Professor Jake Heron, private security expert, team up and spend the next seventy-two hours racing to stop a diabolical serial killer.